Expression of the immunoproteasome subunit β5i in non-small cell lung carcinomas. Issue 5 (17th September 2020) - Kiuchi, Takayuki; Tomaru, Utano; Ishizu, Akihiro; Imagawa, Makoto; Iwasaki, Sari; Suzuki, Akira; Otsuka, Noriyuki; Ohhara, Yoshihito; Kinoshita, Ichiro; Matsuno, Yoshihiro; Dosaka-Akita, Hirotoshi; Kasahara, Masanori
Abstract : Aim: The immunoproteasome is a specific proteasome isoform whose proteolytic activity enhances the generation of antigenic peptides to be presented by major histocompatibility complex class I molecules to CD8 + T cells. Physiologically, it is expressed abundantly in immune cells and is induced in somatic cells by cytokines, especially interferon-γ. Recently, variable expression of immunoproteasomes has been demonstrated in different types of cancers. However, the clinical significance of immunoproteasome expression in malignant tumours is poorly understood. In this study, we performed clinicopathological evaluation of immunoproteasome subunit β5i in non-small cell lung carcinomas (NSCLCs). Methods: Tumour tissues were collected from 155 patients with NSCLCs, and immunohistochemical analysis for β5i was performed in relation to the prognosis of patients. Results: High expression of β5i was found in about 20% of all NSCLCs and was found significantly more frequently (40%) in the adenocarcinoma subset. High expression of β5i was associated with a better 5-year relative survival rate in patients with pStage I to II adenocarcinoma and was also a significant and independent favourable prognostic factor in adenocarcinoma patients. In addition, when we performed in vitro analysis using NSCLC cell lines, combined treatment with the immunoproteasome-specific inhibitor ONX0914 and the proteasome inhibitor MG132 enhanced cell death in β5i-expressing NSCLC cell lines. Conclusion: The expression of immunoproteasome can be explored as both a prognostic factor and a potential therapeutic target in NSCLCs. Since immunoproteasomes have crucial role in the antigen presentation, further studies may help to provide essential knowledge for therapeutic strategies in anticancer immunotherapy.